Short story student-writers: active roles in writing through the use of e-portfolio dossier - Cuesta, Liliana; Rincón, Stella (Colombian Applied Linguistics Journal, 2010)
This article reports the effects of using the genre-process approach and e-portfolio dossier to improve short story writing among senior year students from a state school in Bogotá. This study originated from a need to generate student interest in the development of writing skills and to find instructional strategies that guide learners through each stage of the process. The results of data analysis from this study reveals significant improvements in students’ written production and the emergence of new roles among the learners: they evolved from a passive to an active status which enabled them to become planners, builders and reviewers of their own short story writing process. These new roles helped students reflect on their learning and become better decision makers and critical thinkers. Results from this study also validate the use of e-portfolio dossiers as an effective learning and assessment tool.